Bi-level programming subsidy design for promoting sustainable prefabricated product logistics - Wen Yi; Shining Wu; Lu Zhen; Gregory Chawynski (Cleaner Logistics and Supply Chain)
This paper considers the transportation of prefabricated products in the construction industry. Prefabricated products can be transported by road transport or intermodal transport, the latter of which incurs lower carbon emissions. A construction contractor always selects the transport mode with a lower cost rather than one with a lower carbon emission. A bi-level programming model was formulated to decide the optimal subsidy for intermodal transport to achieve the lowest carbon emissions while accounting for the cost minimization decisions faced by construction contractors who use prefabricated products. A numerical example was conducted to demonstrate the effectiveness of the proposed model. This research is important with regard understanding carbon emissions and how they relate to transportation options for industry.